Protecting children from labor: Muslim scholar's viewpoint and legal provisions in selected Muslim countries - Mohd, Azizah; Nik Mahmod, Nik Ahmad Kamal; Ali Mohamed, Ashgar Ali; Amuda, Yusuff Jelili; Che Mohd Salleh, Marhanum (2016)
Protection of children from labor in Islam is basically based on the general purposes of Islamic law (maqasid al-Shari'ah) as well the spirit of the Shari'ah i.e. securing benefit to the mankind and removing harm from occurring on the people. This paper seeks to examine among others the contemporary Muslim scholar’s viewpoint on child labor under Islamic law as well as legal provisions on protecting children from labor under the laws in selected Muslim countries. This is to provide a sample of child protection from labor under the Islamic perspective and Muslim jurisdiction. The research adopts a qualitative methodology where most of the data are collected in the library. The research found that the Muslim jurists differ on whether a child may be a subject of labor while the Muslim Countries have determined a certain age for a child to be employed in non-hazardous work. It is believed that this paper will be beneficial for reference to all academicians, policy makers and the public as a whole.